Caregivers Role in Fostering Independence of Children with Special Needs at Bhakti Luhur Dormitory - Goa, Lorentius; Tarihoran, Emmeria; Kristeno, Marianus Rago (Ilomata International Journal of Social Science, 2025)
This article explores the role of caregivers in fostering independence among children with special needs at Bhakti Luhur Putra Dormitory. The study focuses on parenting strategies that enhance self-care abilities, which are crucial for improving these children's quality of life and social integration. Despite existing studies on caregiving for children with disabilities, limited attention has been given to institutional settings where personalized care and empowerment-based approaches are applied. This study uses a qualitative research methodology, utilizing interviews, observations, and document analysis to collect data from eleven Bhakti Luhur Putra Dormitory caregivers. Data were collected through semi-structured interviews, participant observations, and document analysis involving eleven caregivers with significant experience. The findings highlight that emotional support, structured training, and personalized care are vital strategies for promoting independence. These approaches foster children's confidence, encourage self-reliance, and help them integrate into broader social environments. This research provides practical insights for improving caregiving practices in institutional contexts. It contributes to the literature by offering a focused understanding of how specific caregiving strategies impact the autonomy of children with special needs. Recommendations include integrating emotional intelligence and structured independence training into caregiver development programs for better developmental outcomes. The study also highlights the importance of adapting care strategies to meet the unique needs of each child, ensuring long-term benefits for their personal growth and social participation.